The Impact of Diabetes Mellitus on the Second Primary Malignancies in Colorectal Cancer Patients - Halamkova, Jana; Kazda, Tomas; Pehalova, Lucie; Gonec, Roman; Kozakova, Sarka; Bohovicova, Lucia; Slaby, Ondrej; Demlova, Regina; Svoboda, Marek; Kiss, Igor (Frontiers in Oncology, 2021)
Introduction All colorectal cancer (CRC) survivors have an increased risk of developing second primary malignancies (SPMs). The association between diabetes mellitus (DM) and the risk of cancer is well known. However, the role of DM and its therapy in the development of SPMs in CRC patients is not well described. Methods In this single-institutional retrospective analysis we identified 1,174 colorectal carcinoma patients, median follow-up 10.1 years, (median age 63 years, 724 men). All patients over 18 years with histologically confirmed CRC who were admitted in the period 1.1. 2003- 31.12.2013 and followed-up till 31.12. 2018 at the Masaryk Memorial Cancer Institute (MMCI) were screened for eligibility. The exclusion criteria were CRC diagnosed at autopsy, lost to follow-up and high risk of development of SPMs due to hereditary cancer syndrome. Tumours are considered multiple primary malignancies if arising in different sites and/or are of a different histology or morphology group. Comparisons of the basic characteristics between the patients with SPM and the patients without SPM were performed as well as comparison of the occurrence of SPMs by the site of diagnosis between the DM and non-DM cohorts and survival analyses. Results A SPM was diagnosed in 234 (20%) patients, DM in 183 (15%) patients. DM was diagnosed in 22.6% of those with SPM vs. in 13.8% of those without SPM (p=0.001). The most common types of SPMs in DM patients were other CRC, kidney, lung, bladder and nonmelanoma skin cancer, but only carcinoma of the liver and bile duct tracts was significantly more common than in the group without DM. Although breast cancer was the second most common in the group with DM, its incidence was lower than in the group without DM, as well as prostate cancer. A significantly higher incidence of SPMs was found in older CRC patients (≥ 65 years) and in those with lower stage colon cancer and DM. No significant difference in DM treatment between those with and without a SPM was observed including analysis of type of insulin. Conclusion CRC patients with diabetes mellitus, especially those with older age, and early stages of colon cancer, should be screened for second primary malignancies more often than the standard population. Patients without DM have longer survival. According to the occurrence of the most common second malignancies, a clinical examination, blood count, and ultrasound of the abdomen is appropriate, together with standard breast and colorectal cancer screening, and lung cancer screening under certain conditions, and should be recommended in CRC survivors especially in patients with intercurrent DM, however the necessary frequency of screening remains unclear.